Careers in criminalization: reentry, recidivism, and repeated incarceration - Western, Bruce (Crime and justice, 2022)
Criminalization is the process by which people are classified by authorities as criminal and become subject to the control of criminal justice agencies—police, courts, and correctional departments. “Careers in criminalization” refers to sustained criminal justice involvement through repeated incarceration and ongoing police and court contact. Careers in criminalization are produced through a mutually reinforcing process of system-induced harms and criminal justice traps that combine to prolong surveillance and penal control. System-induced harms are physical, psychological, and reputational injuries that may be criminogenic or otherwise impede adjustment to community life. Criminal justice traps are cycles of involvement created through intensive surveillance, compliance enforcement, and system marking. The idea of careers in criminalization has special relevance for understanding prisoner reentry, in which criminal justice institutions and officials sustain surveillance and penal control, delaying social integration.